Discrimination of vegetation strata in a multi-layered Mediterranean forest ecosystem using height and intensity information derived from airborne laser scanning - Morsdorf, Felix; Mårell, Anders; Koetz, Benjamin; Cassagne, Nathalie; Pimont, Francois; Rigolot, Eric; Allgöwer, Britta (Remote Sensing of Environment, 2010)
Height and intensity information derived from Airborne Laser Scanning (ALS) was used to obtain a quantitative vertical stratiﬁcation of vegetation in a multi-layered Mediterranean ecosystem. A new methodology for the separation of different vegetation strata was implemented using supervised classiﬁcation of a twodimensional feature space spanned by ALS return height (terrain corrected) and intensity. The classiﬁcation was carried out using Gaussian mixture models tuned on a control plot. The approach was validated using extensive ﬁeld measurements from treated plots, ranging from single vegetation strata to a more complex multi-layered ecosystem. Plot-level canopy proﬁles derived from ALS and from a geometric reconstruction based on ﬁeld measurements were in very good agreement, with correlation coefﬁcients ranging from 0.73 (for complex, 3-layered) to 0.96 (simple, single-layered). In addition, it was possible to derive plot-level information on layer height, vertical extent and coverage with absolute accuracies of some decimetres (simple plots) to a meter (complex plots) for both height and vertical extent and about 10 to 15% for layer coverage. The approach was then used to derive maps of the layer height, vertical extent and percentage of ground cover for a larger area, and classiﬁcation accuracy was evaluated on a per-pixel basis. The method performed best for single-layered plots or dominant layers on multi-layered plots, obtaining an overall accuracy of 80 to 90%. For subdominant layers in the more complex plots, accuracies obtained were as low as 48%. Our results demonstrate the possibility of deriving qualitative (presence and absence of speciﬁc vegetation layers) and quantitative, physical data (height, vertical extent and ground cover) describing the vertical structure of complex multi-layered forest ecosystems using ALS-based height and intensity information
The following values have no corresponding Zotero field: publisher: Elsevier Inc.
Keywords: airborne laser scanning; Canopy proﬁle; cluster analysis; Gaussian mixture models; LiDAR; Multi-layered ecosystems; Shrubland; Supervised classiﬁcation; Vertical stratiﬁcation; Wildland ﬁres